Capital structure of UK SMEs: an integrated understanding - Poutziouris, Panikkos Zata; Markou, Demetris; Glyptis, Loukas; Hadjielias, Elias (My University, 2022)
This study contributes with an integrated understanding of SME capital structure patterns at the nexus of internal (firm-specific) and external environment determinants. The hypotheses draw on pecking order theory (POT), agency theory, and business cycle theories, and estimates are obtained from a data panel of 424 UK SMEs, over a ten-year period. Furthermore, the findings and discussion draw on both static and dynamic models of capital structure. The results between the static and the dynamic model are qualitatively similar, illustrating that firms change their capital structure over time, which is consistent with the POT and agency theory. In contrast to previous results on capital structure choices, the present study reveals that size relates to long-term debt borrowing only in the short-term, and SME growth is not positively linked with gearing ratios. The findings also offer evidence that support macroeconomic conditions as having a nonlinear, convex relationship with the gearing ratios of the sample firms.
Keywords: business cycle; capital structures; firm-specific characteristics; SME financing; SMEs; UK